PEMBUATAN SEDIAAN PAREM DARI KENCUR (Kaemferia galanga L) BERAS (Oriza sativa) DAN SERAI (Cymbopogon citratus)SEBAGAI PENYEMBUHAN LUKA MEMAR, BENGKAK DAN KESELEO - Tamara, Linda; Andriani, Susi; Helmiawati, Yusi (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Background: Kaemferia galanga L is known as a remedy for pain relief muscle disorders empirically. Kaemferia galanga L with Oryza sativa and Cymbopogon citratus can used in a medicinal herb. Kaemferia galanga L has properties as a muscle relaxant, while lemongrass can be efficacious as a headache remedy, cough, stomach pain, diarrhea, body warmers, fever and mosquito repellent. The aim: This research aim to provide the dosage of traditional herb that can be used by the community for the prevention and healt improvement. Method: This research is a descriptive study that was developed from the experience of hereditary regarding the efficacy of kencur, rice and lemongrass for wound healing swelling, bruising and sprains to the skin. In this research, preparations of kencur (Kaemferia galanga L), rice (Oryza sativa) and lemongrass (Cymbopogon citratus) in the form parem puck through the process of drying for 1 day using water-soluble. Parem made by adding of 100 gram and 200 gram simplisia rice (Oryza sativa), 25 ml of water, parem obtained are 100 grams and produces 10 each ringed with a weight of 10 grams. Result: Tests organoleptic for 3 weeks with results showing that there is no negative changes from the shape, color, smell, taste and fungal growth. Conclusion: In this research managed to make preparations in the form parem pieces that can last for 3 weeks.